Pengaruh Penambahan Asam Sitrat Terhadap Proses Non-Enzimatik Browning Jus Buah Pir Yali (Pyrus bretschneideri Rehd.) - Victoria Agatha Angela Sirait; Zulkifli Zulkifli; Tundjung Tripeni Handayani; Martha Lulus Lande (Politeknik Negeri Lampung., 2018)
The purpose of this study was to find out how effective citric acid is against the nonenzymaticprocess of browning Yali Pear fruit juice (Pyrus bretschneideri Rehd. Theresearch was conducted in a complete randomized design consisting of 5 replications. Thenon-enzymatic browning inhibition process was tested with citric acid treatment as the mainfactor with five concentrations ie 0% w/v, 2,5% w/v, 5% w/v, 7,5% w/v and 10% w/v.Qualitative parameters were dehydrogenase enzyme activity and reducing sugar level.Quantitative parameters were browning index and total soluble carbohydrate content.Levene test, analysis of variance, and Tukey test were performed at 5% significant level. Theresults showed that decrease in dehydrogenase enzyme activity occurs along with increasingthe concentration of citric acid. The level of reducing sugar has increased along with theincrease of citric acid concentration. The 7,5% w/v citric acid concentration effectivelyinhibited non-enzymatic browning of Yali Pear juice with a 21% reduction in the browningindex. Total soluble carbohydrate content increased 7% at 7.5% w/v citric acidconcentration. From the results of the study it was concluded that citric acid at 7,5% w / vconcentration was the inhibitor of non-enzymatic browning and dehydrogenase enzymeactivity, but stimulator of total soluble carbohydrate and reducing sugar level.